Fairness and futurity essays on environmental sustainability and social justice - edited by Andrew Dobson (Oxford Oxford University Press, 1999)
This book brings together leading international figures in political theory and sociology, as well as representatives from the political community, to consider the normative issues at stake in the relationship between environmental sustainability and social justice. These essays emerged from three intensive seminars which brought these distinct groups into fruitful contact.
Includes bibliographical references (p. [310]-324) and index.
Keywords: Sustainable development